2022
DOI: 10.3389/fimmu.2022.958616
|View full text |Cite
|
Sign up to set email alerts
|

T cell-specific constitutive active SHP2 enhances T cell memory formation and reduces T cell activation

Abstract: Upon antigen recognition by the T cell receptor (TCR), a complex signaling network orchestrated by protein-tyrosine kinases (PTKs) and protein-tyrosine phosphatases (PTPs) regulates the transmission of the extracellular signal to the nucleus. The role of the PTPs Src-homology 2 (SH2) domain-containing phosphatase 1 (SHP1, Ptpn6) and Src-homology 2 (SH2) domain-containing phosphatase 2 (SHP2, Ptpn11) have been studied in various cell types including T cells. Whereas SHP1 acts as an essential negative regulator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 66 publications
(85 reference statements)
0
2
1
Order By: Relevance
“…Animal experiments have also confirmed that LHQW can reduce the viral load in the lungs of mice with viral pneumonia, reduce the expression of inflammatory factors in the lungs, and improve lung injury (Xia et al, 2020;Su et al, 2022). It is well known that viral clearance in the lung depends mainly on lymphocytes and macrophages (Bedi et al, 2022;Cammann et al, 2022;Harris and Borg, 2022;McGee et al, 2022;Verma et al, 2022;Wei et al, 2022;Zhang H. et al, 2022;Zhang M. et al, 2022); however, the present findings do not clarify how LHQW reduces the viral load in the lung and improves lung injury with viral pneumonia.…”
Section: Introductioncontrasting
confidence: 67%
“…Animal experiments have also confirmed that LHQW can reduce the viral load in the lungs of mice with viral pneumonia, reduce the expression of inflammatory factors in the lungs, and improve lung injury (Xia et al, 2020;Su et al, 2022). It is well known that viral clearance in the lung depends mainly on lymphocytes and macrophages (Bedi et al, 2022;Cammann et al, 2022;Harris and Borg, 2022;McGee et al, 2022;Verma et al, 2022;Wei et al, 2022;Zhang H. et al, 2022;Zhang M. et al, 2022); however, the present findings do not clarify how LHQW reduces the viral load in the lung and improves lung injury with viral pneumonia.…”
Section: Introductioncontrasting
confidence: 67%
“…PD-1 engagement with PD-L1 or PD-L2 triggers inhibitory signaling through its cytoplasmic domain, involving ITIM and ITSM motifs that recruit SHP2. The intricate interplay of SHP2 within the PD-1 pathway showcases its multifaceted influence on T-cell activation and immune response regulation, emphasizing its significance as a key mediator of immune checkpoint modulation [7,38,39].…”
Section: The Role Of Shp2 In Tumor Antigen Presentation In Cancer Cellsmentioning
confidence: 99%
“…SHP2 deficiency in T cells can lead to impaired TCR signaling and defective immune responses. The interplay of SHP2 with PD-1, including feedback mechanisms, and its broader impact on TCR signaling and immune regulation continue to be active areas of research, influencing our understanding of T-cell responses, especially in the context of cancer immunotherapy [3,39,41].…”
Section: Shp2 In Tcr Signaling and Ras/mapk Signaling Pathwaysmentioning
confidence: 99%